GIS-material for the archaeological project: Settlement remains by burial ground RAÄ 178 - Bjursby - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned construction of a single-family house and an access road within the property Bjursby 1:2, Östra Harg parish, Linköping municipality, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a preliminary investigation. Prehistoric settlement remains were discovered close by a burial ground (RAÄ 178). No remains were found on the site of the planned house, but the road will pass through the newly found settlement. To avoid affecting the archaeological remains, UV Öst suggests the road to be moved c. 30 m to the south.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to conclude whether any archaeological remains were going to be affected by the development works.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har utfört en arkeologisk förundersökning inom fastigheten Bjursby 1:2, Östra Hargs socken, Linköpings kommun. Anledningen var planer på att uppföra ett enbostadshus samt en tillfartsväg inom ovanstående fastighet. Vid förundersökningen påträffades en förhistorisk boplatslämning belägen strax nedanför ett gravfält (RAÄ 178). På den plats där bostadshuset planeras påträffades inga spår av fornlämningar, däremot kommer den planerade vägen att passera rakt igenom den nu upptäckta boplatsen. För att undvika ingrepp inom fornlämningen föreslår UV Öst att vägsträckningen flyttas ett 30-tal meter söderut.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska förundersökningen var att avgöra om de planerade arbetena kunde komma att beröra en lagskyddad fornlämning.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Boplatsspår vid gravfältet RAÄ 178 - Bjursby
Keywords: Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive